A neural origin for central nervous system germ cell tumours - Tan, Christopher Callum Lee (2013)
Germ cell tumour (GCT) is the collective term for several subtypes of tumour. GCTs most commonly occur in the testis or ovary around puberty, but they also occur at several non-gonadal locations in the human body. These so-called “extra-gonadal” GCTs have the same histology and protein markers as those that arise at gonadal locations. This observation prompted several hypotheses to explain where these tumours come from. Extragonadal locations include the base of the spine (sacrococcygeal region), the abdomen (retroperitoneum), the chest cavity (mediastinum), and the brain (intracranial). The origin of central nervous system (CNS) GCTs is the main focus of this thesis. The most widely accepted hypothesis for extragonadal GCTs was originally proposed by Gunnar Teilum in 1965. Teilum proposed that all GCTs that arise in the human body have a common cell of origin. Teilum’s experiments showed that a germ cell progenitor could give rise to a GCT. This was one piece of evidence that led him to suggest that since GCTs in the testis and ovary arise from a germ cell progenitor, perhaps GCTs in other locations also arise from these progenitors. For extra-gonadal GCTs, these progenitors are thought to mismigrate and become trapped at several locations around the body. The regions where GCTs occur are suggested to be those regions where these progenitors have become trapped, such as the brain. However, research into pluripotency has revealed a mechanism of generating a GCT from an endogenous population of cells isolated from the brain, neural stem cells, using the upregulation of only a single gene, Oct4. In this thesis I test the hypothesis that CNS GCTs may arise from a neural progenitor, and not just from a germ-cell progenitor. I will use several strategies to test this hypothesis with different methodologies. Published literature is first used to review and re-analyse the case for a neural cell of origin for CNS GCTs. This hypothesis is then experimentally tested in subsequent chapters, culminating in a unifying hypothesis for how CNS GCTs may arise.